Advancing the HIV cure agenda: the next 5 years. Issue 1 (February 2015) - Thornhill, John; Fidler, Sarah; Frater, John
Abstract : Purpose of review: To explore how ethical considerations, improved diagnostics and data from clinical trials might see the lowering of some of the barriers blocking a cure for HIV infection over the next 5 years. Recent findings: Despite the recent well publicized but eventually disappointing case reports, there remains only one successful HIV cure, the 'Berlin patient'. We will review the data suggesting that more potent agents might achieve in-vivo viral activation and explore the tantalizing phenomenon of 'posttreatment control' following treatment in primary HIV infection. We will also explore how new assays and novel interventions might move the field forward. Summary: There is a need for new agents that can be safely tested to impact the viral reservoir, a more meaningful understanding of how to assay patient samples, and research into mechanisms behind how the reservoir is established and impacted by therapy. With HIV+ve individuals responding so well to antiretroviral therapy, new trials must be tested hand-in-hand with guidance from patient representatives, especially with respect to determining the acceptable risk. The road to a cure is going to be difficult, but it is vital that inevitable disappointments do not detract from the final goal, which remains worth striving for.